2017
DOI: 10.1101/140178
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivophenotyping of Parkinson-specific stem cells reveals increased a-Synuclein levels but no spreading

Abstract: Parkinson′s disease is a progressive age-associated neurological disorder. One of the major neuropathological hallmarks of Parkinson’s disease is the appearance of protein aggregates, mainly consisting of the protein alpha-Synuclein. These aggregates have been described both in genetic as well as idiopathic forms of the disease. Currently, Parkinson’s disease patient-specific induced pluripotent stem cells (iPSCs) are mainly used for in vitro disease modeling or for experimental cell replacement approaches. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…It is particularly interesting to note a recent study that transplanted human iPSC-derived neurons bearing a mutation associated with PD into mouse brain. 87,88 The study investigated whether iPSCs may have another role in in vivo disease modelling. However, despite increased levels of α-synuclein in the transplanted human neurons, there was an absence of cell spreading or aggregation (which would typify the disease phenotype), and so the authors concluded that “our results support the hypothesis that there might be a species barrier between human to mouse concerning alpha-synuclein spreading.”
Figure 1.Application of models used in Parkinson’s disease (PD) research over the past 30 years.
…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…It is particularly interesting to note a recent study that transplanted human iPSC-derived neurons bearing a mutation associated with PD into mouse brain. 87,88 The study investigated whether iPSCs may have another role in in vivo disease modelling. However, despite increased levels of α-synuclein in the transplanted human neurons, there was an absence of cell spreading or aggregation (which would typify the disease phenotype), and so the authors concluded that “our results support the hypothesis that there might be a species barrier between human to mouse concerning alpha-synuclein spreading.”
Figure 1.Application of models used in Parkinson’s disease (PD) research over the past 30 years.
…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…Whether these findings are reproducible with another analytical method, still needs to be explored further. Nevertheless, the assessment of PD-associated pathologies, such as the synucleinopathies, in human-specific advanced cell culture models is crucial due to the inherent differences between human and mouse mDAN vulnerability and as existing murine transgenic models have not been efficient in developing an accurate representation of the underlying disease mechanisms (Byers et al, 2012;Burbulla et al, 2017;Hemmer et al, 2018;Koh et al, 2018). In the study of Smits et al (2019b) a significant increase of FOXA2positive progenitor cells in the patient-specific organoids was demonstrated.…”
Section: Disease Modeling In Midbrain-specific Organoidsmentioning
confidence: 99%
“…Considering the limited numbers of TH-positive neurons present in both control and PD grafts it is desirable to examine in future studies longer time points, exceeding 6 months after transplantation, which is a challenging task taking into consideration the increased mortality rate of the 6-OHDA lesioned NOD/SCID mice. Long-term studies are also needed to clarify whether the elevation in αSyn immunoreactivity seen in PD grafts (this study with p.A53T-αSyn grafts and [468] with LRRK2-G2019S grafts) -a phenotype that cannot be attributed to their more immature state -would eventually result in a pathological phenotype with formation of protein aggregates in mature neurons.…”
Section: Main Findings and Discussionmentioning
confidence: 99%
“…The only study reported so far used DAergic neurons carrying the G2019S-LRRK2 mutation, suggested that these cells survive in vivo in the mouse brain for 11 weeks, but up-regulate human αSyn which is believed to be the first step towards induction of pathology [468]. However, the increased human αSyn levels fail to induce spreading or aggregation in the mouse brain.…”
Section: Autologous Cell Transplantationmentioning
confidence: 99%